GENDER REPRESENTATION IN ENGLISH TEXTBOOKS NEW FRONTIERS 2 FOR GRADE EIGHT AT SMP - Agi Julianto Martuah Purba; Sahlan Tampubolon; Sondang Manik; Nasiba Komilovna (Merwin Publisher, 2025)
Gender is a significant social construct that influences various aspects of life, including education and media representation. This study investigates gender representation in the New Frontiers 2 English textbook for Grade 8 students at SMP Swasta Methodist Tanjung Morawa. The research employs a qualitative descriptive method. Using Logsdon’s (1985) framework, which identifies six aspects of gender representation, the study analyzes the prevalence and portrayal of male and female characters in terms of pictures, mentions, roles, games, role models, and naming patterns. The findings reveal imbalances in representation, with males dominating leadership and technical roles, while females are more often linked to descriptive or emotional contexts. This highlights the need for equitable gender portrayals in textbooks to foster inclusive and unbiased learning environments. The study emphasizes the importance of critically evaluating educational materials to ensure they promote gender equality, aligning with Indonesia’s commitment to creating equitable learning opportunities.